Mapping urban methane sources in Paris, France - Defratyka, Sara M.; Paris, Jean-Daniel; Yver-Kwok, Camille; Fernandez, Julianne M.; Korbeń, Piotr; Bousquet, Philippe (Environmental science & technology, 2021)
Megacities, with their large and complex infrastructures, are significant sources of methane emissions. To develop a simple, low-cost methodology to quantify these globally important methane sources, this study focuses on mobile measurements of methane (CH4) and its isotopic composition in Paris. Data collected between September 2018 to March 2019 resulted in 17 days of measurements, which provided spatial distribution of street-level methane mixing ratios, source type identification, and emission quantification. Consequently, 90 potential leaks were detected in Paris sorted into three leak categories: natural gas distribution network emissions (63%), sewage network emissions (33%), and emissions from heating furnaces of buildings (4%). The latter category has not previously been reported in urban methane studies. Accounting for the detectable emissions from the ground, the total estimated CH4 emission rate of Paris was 5000 L/min (190 t/yr), with the largest contribution from gas leaks (56%). This ranks Paris as a city with medium CH4 emissions. Two areas of clusters were found, where 22% and 56% of the total potential emissions of Paris were observed. Our findings suggest that the natural gas distribution network, the sewage system, and furnaces of buildings are ideal targets for street-level CH4 emission reduction efforts for Paris.